The Effectiveness of Educational Booklets for Pregnant Women with Hyperemesis Grafidarum on Blood Sugar Levels While in the Working Area of the Belimbing Padang Health Center - Metri Lidya; Wiwi Sartika (POLTEKKES KEMENKES PADANG, 2023)
Pregnancy is a reproductive process that needs special care in order to achieve safe and good delivery, giving birth to a healthy baby in hopes of lowering baby and mother mortality. Gravidarum hyperemesis is excessive nausea and vomiting that leads to fluid and electrolyte deficiencies, weight loss, aceonuria, and nutritional deficiencies. This feeling of nausea is caused by increased levels of the hormones estrogen and Chorionic Gonadotropin Hormone (HCG) in serum reduced gastric changes (Ministry of Health, 2013). One of the predisposing factors associated with the increased risk of morning sickness and physiological hyperemesis is not yet clear, and the central nervous system or emptying of gravidarum is gestational diabetes mellitus at knowing the effectiveness of booklet-based education in mothers with hyperemesis Grafidarum to temporary blood sugar levels in kuranji village in the working area of Public health center Belimbing Padang. The type of research is a Pre – Experimental Design with the One - Group Pretest and Posttest Design. Analyzing the Application of Booklet-Based Education Model in Pregnant Women with Grafidarum Hyperemesis on temporary Blood Sugar Levels in Kuranji Village Padang. Data is processed by editing, coding, entry, cleaning and analyzed by univariate and bivariate . More than half (55%) of pregnant women experienced moderate levels of hyperemesis, and 65% of blood sugar levels of pregnant women with hyperemesis were in abnormal conditions before given the booklet education. Most (70%) of pregnant women's blood sugar levels are within normal limits after given the educational booklets. Bivariate analysis showed that educational booklet about hyperemesis has an influence on the blood sugar levels of pregnant women in the working area of The Belimbing public Health Center.